(untitled) - Schaffer, Robert H. (San Francisco, CA, 2005)
Rapid Results! shows how to make large-scale changes succeed by using 100-day results-producing projects to develop this vital implementation capability. Written by Robert H. Schaffer, Ronald N. Ashkenas, and their associates—leaders in the field of change management—Rapid Results! describes an approach that has been field-tested by real organizations of every size and description to improve performance and speed the pace of change.
Keywords: Organizational change,Organizational effectiveness,Thay đổi tổ chức,Tổ chức hiệu quả; Management,Quản lý